Green energy through the LCOE indicator. (November 2022) - Filimonova, I.V.; Kozhevin, V.D.; Provornaya, I.V.; Komarova, A.V.; Nemov, V.Y.
Abstract: Renewable energy development in Russia follows global trends with some delay. However, at the moment, a renewable energy production cluster has been formed, and the commissioning of 8.4 GW of capacity is planned until 2028, marking more than a twofold drop in capital expenditures under the power supply contracts program. The article calculated the LCOE indicator for three types of generation of wind farms, solar and small hydropower plants in 2021 based on the results of capacity selection at power supply contracts auctions, describes the primary factors and drivers of the decline in this indicator. Utilizing the chain substitution method, factors' contribution to the change in the LCOE indicator in 2021 were calculated, which marked more than 105 % of the contribution of capital expenditures to the change in the indicator. Analysis of the last power supply contracts program revealed the Efficiency indicator of a renewable energy generating facility (analogue of LCOE) dropped to 0, 023 $/kWh for wind projects due to increased competition in Russia. It is shown that Russia notes similar worldwide trends of new solar and wind generation price reduction.